Applying Tools and Techniques of Natural Language Processing to the Creation of Resources for Less Commonly Taught Languages - McShane, Marjorie (IALLT Journal of Language Learning Technologies, 2003)
This paper proposes that research results from the area of natural language processing could effectively be applied to creating software to facilitate the development oflanguage learning materials for anynaturallanguage. We will suggest that a knowledge-elicitation system called Boas, which was originally created to support a machine-translation application, could be modified to support language-learning ends. Boas leads a speaker of any natural Ianguage, who is not necessarily trained in linguistics, through a series of pedagogically-supported questionnaires, the responses to which constitute a" profile" of the language. This profile includes morphological, lexical and syntactic information. Once this structured profile is created, it can feed into virtually any type of system, including one to support language learning. Creating languagelearning software using a system like this would be efficient in two ways: first, it would exploit extant cutting-edge research and technologies in naturallanguage processin and second, it would permit a single tool to be used for all languages, including less commonly taught ones, for which limited funding for resource development is a bottleneck.